How Should We Address Medical Conspiracy Theories? An Assessment of Strategies - Andrade, Gabriel; Lugo-Ocando, Jairo (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2024)
Although medical conspiracy theories have existed for at least two centuries, they have become more popular and persistent in recent times. This has become a pressing problem for medical practice, as such irrational beliefs may be an obstacle to important medical procedures, such as vaccination. While there is scholarly agreement that the problem of medical conspiracy theories needs to be addressed, there is no consensus on what is the best approach. In this article, we assess some strategies. Although there are risks involved, it is important to engage with medical conspiracy theories and rebut them. However, the proposal to do so as part of “cognitive infiltration” is too risky. Media outlets have a major role to play in the rebuttal of medical conspiracy theories, but it is important for journalists not to politicize this task. Two additional long-term strategies are also necessary: stimulation of critical thinking in education, and empowerment of traditionally marginalized groups.